Seaweed extract as a biostimulant for legume crop, green gram - Jayashree, N. Thangaraju*, R. Kavipriya, P. K. Dhanalakshmi, S. (Journal of Ecobiotechnology, 2011)
The aim of this research is to investigate the effect of seaweed extracts obtained from the marine green algae, Ulva lactuca Linnaeus, Caulerpa scalpelliformis (R. Brown ex Turner) C. Agardh, brown algae Sargassum plagiophyllum C. Agardh, Turbinaria conoides (J. Agardh) Kutzing, Padina tetrastromatica Hauck, Dictyota dichotama (Hudson) J. V. Lamouroux on the stimulate germination, growth parameters of the Vigna radiata. The present study reveals the seeds germination, fresh weight and dry weight of shoots and roots. These results suggested that seaweed extracts stronger induce seed germination and growth parameters.